Genocidal Practices and Paramilitary Intimidation to the Intellectual Movement at the University of Cordoba, Colombia - Taborda Caro, Dra. María Alejandra (2018)
The University of Cordoba in Colombia has been declared as a beneficiary of collective reparation, a unique sui generis case in the world. The plan contemplates 48 measures, among them providing the alma mater with a new university statute to replace the one that the United Self-Defense Forces of Colombia (AUC) implemented between the 1990s and the beginning of 2000, by what was called "the bloody and merciless occupation" in which sixteen members of this institution were assassinated, and another group of at least six professors had to go into exile. In the department of Cordoba, two phenomena of opposite sign have been mixed; they facilitated genocidal practices. On the one hand, the political clientelism that traps an electorate in extreme poverty captivated a cacique who concentrated a territorial power. On the other hand, a group that acted under the following triad: landowners, livestock and drug trafficking.  Thus, one of the most impressive concentrations of land in the contemporary history of the country was consolidated. At the end of the last decade, newspapers headlined that being an educator in Cordoba was "the most dangerous profession.” This paper is part of a wider investigation that gives an account of the strategies of paramilitary groups to take over State universities as a war maneuver, using academic control of unions and student movements. Methodologically, we proceed through an analysis of prescriptive, testimonial, journalistic (such as investigations, reports, opinion columns), and academic (research articles, books, reports of undergraduate and graduate studies) documents, as well as in-depth interviews.